2021
DOI: 10.1111/pin.13182
|View full text |Cite
|
Sign up to set email alerts
|

AID is a poor prognostic marker of high‐grade B‐cell lymphoma with MYC and BCL2 and/or BCL6 rearrangements

Abstract: Diffuse large B-cell lymphoma with MYC rearrangement is defined as double/ triple-hit lymphoma (DHL/THL) or single-hit lymphoma (SHL) by the inclusion of the BCL2 and BCL6 rearrangements status. DHL/THL is called as "highgrade B-cell lymphoma with MYC and BCL2 and/or BCL6 rearrangements" in the World Health Organization 2017 Classification of Tumors of Hematopoietic and Lymphoid Tissues. To find a prognostic biomarker of DHL/THL, we firstly examined 19 cases (molecular analysis series;10 cases of DHL/THL and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…There are many markers with prognostic value in DLBCL. Our group has highlighted some such as ENO3 [17,142], PTX3 and CD163 [143], RGS1 [144], CASP8 and TNFAIP8 [99], and AID [145]. All these markers will have to be validated in other series in future.…”
Section: Discussionmentioning
confidence: 99%
“…There are many markers with prognostic value in DLBCL. Our group has highlighted some such as ENO3 [17,142], PTX3 and CD163 [143], RGS1 [144], CASP8 and TNFAIP8 [99], and AID [145]. All these markers will have to be validated in other series in future.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found for the TNFAIP8 marker [ 12 ]. We also previously described the gene expression of High-grade B-cell lymphoma [ 35 ]. In this research, we identified seven genes that predicted the overall survival of patients of non-High-grade B-cell lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…BCL6 upregulates Activation-induced cytidine deaminase (AICDA, also known as AID), which is responsible for germinal center-associated somatic hypermutation (SHM). 32 , 77 - 83 BCL6 -null mice lack germinal centers. 84 , 85 Therefore, BCL6 is a key oncogene in B-cell lymphomagenesis.…”
Section: Bcl6 Transcription Repressormentioning
confidence: 99%